(untitled) (INNOVATIVE ECONOMY, 2026)
Pasichnyk T.O. HORIZONTAL INNOVATIONS AND ENDOGENOUS GROWTH: ASSUMPTIONS, MECHANISMS, AND DEBATES Purpose. The aim of the article is to systematize the key assumptions of P. Romer’s horizontal innovation models, this paper systematizes the key assumptions of Paul Romer’s horizontal innovation models, shows how these assumptions underpin the main theoretical conclusions about the role of R&D and firms’ innovative activity in economic growth, and outlines the major issues and debates in innovation, competition, and patent policy that follow from this framework. Methodology of research. The study employs analysis and synthesis to select and integrate the literature on horizontal innovation models and related contemporary debates; logical and deductive analysis to trace causal links between model assumptions and growth outcomes; and comparative analysis to contrast the structural elements of the “knowledge-driven” specification and the “lab-equipment” model. Findings. The paper summarizes the core assumptions of Paul Romer-type horizontal innovation models: the nonrivalry of ideas; partial excludability (notably via patent protection); imperfect competition and firms’ market power; the “love-for-variety” mechanism; and an aggregate R&D production function that links research inputs to the arrival of new designs. The analysis shows that innovation is driven by private incentives (expected monopoly rents), while technological progress is interpreted as an expansion in the set of designs – or, equivalently, the number of varieties of intermediate goods – which raises productivity in final-goods production. The two specifications are shown to share a common structure but differ fundamentally in the form of the R&D production function, particularly in how the accumulated stock of knowledge affects research productivity. The paper also highlights the main debates associated with these models, including assumptions about R&D productivity, the trade-off between competition and innovation incentives, the empirical relevance of scale effects, and the inefficiency of decentralized equilibrium and its sources. Originality. The study clarifies how the “knowledge-driven” and “lab-equipment” specifications differ in their R&D technologies and in the role assigned to the knowledge stock in determining research productivity. In addition, it systematizes the key tensions and contested policy implications arising from this theoretical framework. Practical value. The research results provide a structured basis for the appropriate use of Paul Romer-type horizontal innovation models in applied analysis and economic policy design. In particular, they can serve as a methodological tool for assessing and comparing alternative policy scenarios (R&D support, the design of intellectual property institutions, competition policy, etc.). Key words: economic growth, innovative development, patents, R&D, horizontal innovations, technological progress, endogenous growth models, scale effects.